Information Technologies for Presentation of Bulgarian-Indian Cooperation in a Virtual Museum - Bogdanova, Galina; Atanasova, Violina; Todorov, Todor (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2011)
We investigate digitalization and security of the Bulgarian and Indian cultural artifacts in multimedia archive. In the paper we describe project implementation and methods for intellectual property protection that are result of bilateral cultural and scientific cooperation between research-workers in India and Bulgaria.